1987
DOI: 10.1002/ana.410220215
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow in down's syndrome

Abstract: Regional cerebral blood flow was measured in 14 patients with Down's syndrome, in 46 patients with Alzheimer's disease and senile dementia of the Alzheimer type, and in 114 age-matched controls, using the xenon 133 inhalation technique. Cerebral blood flow was reduced in 13 of 14 Down's patients by a mean of 16.8 +/- 2.5% from expected age-matched normal values. Degrees of regional cerebral blood flow reduction did not differ among the frontal, temporal, parietal, and occipital regions in both cerebral hemisph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Schwartz et al (1983) and Cutler (1986) reported higher than normal cerebral GMR in a small number of young DS individuals, but Schapiro et al (1990) failed to find any GMR differences between DS and a control sample. Melamed, Mildworf, Sharav, Belenky, and Wertman (1987) reported a decrease in cerebral blood flow in DS. Both the Schapiro et al and the Melamed et al studies, however, were conducted with subjects at rest, a condition not likely to accentuate any functional differences.…”
mentioning
confidence: 97%
“…Schwartz et al (1983) and Cutler (1986) reported higher than normal cerebral GMR in a small number of young DS individuals, but Schapiro et al (1990) failed to find any GMR differences between DS and a control sample. Melamed, Mildworf, Sharav, Belenky, and Wertman (1987) reported a decrease in cerebral blood flow in DS. Both the Schapiro et al and the Melamed et al studies, however, were conducted with subjects at rest, a condition not likely to accentuate any functional differences.…”
mentioning
confidence: 97%